2014
DOI: 10.3146/ps13-21.1
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Surrogate Reduction Using Industrial Peanut Dry Roasting Parameters

Abstract: Studies were conducted to evaluate the effectiveness of industrial peanut dry roasting parameters in Salmonella reduction using a Salmonella surrogate, Enterococcus faecium, which is slightly more heat tolerant than Salmonella. Runner-type peanuts were inoculated with E. faecium and roasted in a laboratory scale roaster simulator in which temperature, airflow, airflow direction and bed depth were highly controlled, allowing for conditions that duplicate industrial dry roasting. Temperature data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Unpublished Conagra Brands studies indicated there is a loss of 31% moisture when brined sunflower seeds are hot-air roasted at 1358C for 20 min. Although the water activity of peanuts before roasting in Poirier et al (36) is comparable to our brined sunflower seeds, the differences in moisture loss between both studies (4.4 versus 31%) could account for the observed differences in heat resistance of Salmonella. Our estimated product temperature corresponding to a minimum of a 4-and 5-log reduction in Salmonella was lower (77.8 and 85.88C, respectively) compared with that of Poirier et al (36).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Unpublished Conagra Brands studies indicated there is a loss of 31% moisture when brined sunflower seeds are hot-air roasted at 1358C for 20 min. Although the water activity of peanuts before roasting in Poirier et al (36) is comparable to our brined sunflower seeds, the differences in moisture loss between both studies (4.4 versus 31%) could account for the observed differences in heat resistance of Salmonella. Our estimated product temperature corresponding to a minimum of a 4-and 5-log reduction in Salmonella was lower (77.8 and 85.88C, respectively) compared with that of Poirier et al (36).…”
Section: Discussioncontrasting
confidence: 45%
“…E. faecium NRRL B-2354 has been commonly used as a surrogate organism for Salmonella Enteritidis phage type 30 for performing validation of thermal treatments for almonds (35). Although performing a study with a surrogate such as E. faecium is outside the scope of our research, it is worth discussing the findings of Poirier et al (36) because the initial water activity of peanuts before roasting was similar to that of sunflower seeds in our study. Poirier et al (36) noted the water activity of the peanuts reduced from 0.73 a w to 0.33 to 0.13 a w , whereas the moisture content of the peanuts decreased from 6.1 to 1.7%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The peanuts had been cured, shelled, sized using standard screens, blanched and stored utilizing standard industry practices prior to delivery to the USDA ARS Market Quality & Handling Research Unit at North Carolina State University (Raleigh, NC, USA). A pilot plant scale roaster previously described (Poirier, Sanders, & Davis, 2014) built by the Bühler Aeroglide Corporation (Cary, NC, USA) with an adjustable air flow rate (up to 1.27 m/s), air flow direction, bed depth, and temperature control (up to 204 ºC) was used for the dry roasting. The air flow direction was changed from up-flow to down-flow at the half point of the roasting time.…”
Section: Methodsmentioning
confidence: 99%
“…These conventional methods of roasting are uncontrolled, inefficient, energy and time consuming and provide a very un-hygienic environment to the operators such as direct exposure to heat radiations and smoke. On an industrial scale, groundnuts are roasted either using gas-fired revolving oven or continuous or batch type roasters which offer more flexible options for precisely controlling the process conditions like temperature, time and product flow rate, ensuring a uniformly processed product [10]. However, these large scale units are economically out-of-reach for small to medium scale farming communities accompanied by the additional burden of escalating fossil fuel prices that upsurges the processing cost.…”
Section: Introductionmentioning
confidence: 99%